Development of Dicationic Bisguanidine-Arylfuran Derivatives as Potent Agents against Gram-Negative Bacteria - Catarina Bourgard; Diego Rodríguez-Hernández; Anastasia Rudenko; Carolin Rutgersson; Martin Palm; D. G. Joakim Larsson; Anne Farewell; Morten Grøtli; Per Sunnerhagen (MDPI AG, 2022)
Antibiotic resistance among bacteria is a growing global challenge. A major reason for this is the limited progress in developing new classes of antibiotics active against Gram-negative bacteria. Here, we investigate the antibacterial activity of a dicationic bisguanidine-arylfuran, originally developed as an antitrypanosomal agent, and new derivatives thereof. The compounds showed good activity (EC50 2-20 µM) against antibiotic-resistant isolates of the Gram-negative members of the ESKAPE group (Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterobacter spp.) and Escherichia coli with different antibiotic susceptibility patterns, including ESBL isolates. Cytotoxicity was moderate, and several of the new derivatives were less cytotoxic than the lead molecule, offering better selectivity indices (40-80 for several ESKAPE isolates). The molecular mechanism for the antibacterial activity of these molecules is unknown, but sensitivity profiling against human ESKAPE isolates and E. coli collections with known susceptibility patterns against established antibiotics indicates that it is distinct from lactam and quinolone antibiotics.